Implicación del artículo 278 inciso 7 del Código de la Democracia durante las elecciones seccionales del año 2023 en el Cantón Loja - André Cuesta, Julio Walter (2023)
The present research work aims to determine the implication of article 278 clause 7 of the Code of Democracy during the sectional elections of 2023 in Loja canton. With this study, we seek to identify the effectiveness of the institutional control mechanisms over the acts of early electoral campaign, as well as to establish if there are legal gaps that prevent the correct application of the article. In addition, it is intended to propose improvements to control and regulate more effectively the acts of electoral campaign, proposed for each process. In this sense, a qualitative methodology has been applied in this research, which allowed to gather information from interviews with experts in the field and observation sheets. In this way, contrasted and reliable information has been obtained to carry out the corresponding analysis. Among the main results obtained, it has been determined that more than 75% of the candidates who participated in the 2023 sectional elections used pseudonyms and carried out acts of early campaigning, taking advantage of the existing legal loopholes. This fact represents a great problem, since these early campaign actions cannot be controlled or sanctioned due to the institutional limitations existing in Consejo Nacional Electoral (National Electoral Council.) Therefore, it is crucial to establish effective measures to control and regulate early campaigning in order to guarantee a fair and transparent electoral process. Based on the results obtained, a series of improvements can be proposed to allow a better regulation and control of the acts of early campaigning, in order to guarantee the effective compliance with article 278 paragraph 7 of the Democracy Code.